Analisis Kepuasan Pengguna Aplikasi Lazada Berbasis Mobile Melalui Pendekatan End-User Computing Satisfaction - Sanjaya, M Rudi Sanjaya; Bayu Wijaya Putra; Annisa Khoiriah (AI Society & STMIK Indonesia, 2025)
The process of conducting business online using the internet and network-connected devices, such as the Lazada platform, is known as e-commerce, or electronic commerce. There is a decrease in the quantity of users on Lazada. The degree of consumer happiness is one of the many variables that may be causing this reduction. The degree to which a customer's expectations and actual product usage experience align is a key indicator of customer happiness. The purpose of this study is to assess users' satisfaction levels with the Lazada application. This study employs a single technique, End-User Computing happiness (EUCS), to measure customer happiness. EUCS includes multiple characteristics, including content, correctness, format, timeliness, and ease of use. Based on the responses from 115 participants in the research questionnaire, these five factors fell into the satisfied group.